Factors influencing the classification accuracy of triage nurses in emergency department: analysis of triage nurses' characteristics - Yon Hee Seo; Kangbum Lee; Kyeongmin Jang (BMC, 2024)
Abstract Background Triage nurses play a vital role in emergency departments (Eds), with the accuracy of the triage nurse significantly impacting patient care and departmental efficiency. However, there is a lack of exploration into whether the time it takes for triage nurses to triage patients affects accuracy. Method This study analyzed the electronic medical records of 787 patients and the characteristics of triage nurses, using statistical methods to determine factors affecting classification accuracy. Data were collected from a single general hospital between November 1 and November 30, 2023. Results Findings revealed an 84.9% accuracy rate. Longer clinical experience (p = .001, CI = 1.094-2.052), as well as extended classification time (p = .002, CI = 1.338-2.916), significantly improved accuracy. Age and gender had no notable effect. Conclusion Enhancing triage nurse experience and allowing adequate classification time can improve accuracy, optimizing patient care and ED operations.